'Here, I'm not at ease': anthropological perspectives on community resilience. Issue 2 (April 2014) - Barrios, Roberto E.
<x xml:space="preserve">Abstract</x> A number of recent studies on disaster reconstruction have focused on the concept of community resilience and its importance in the recovery of communities from collective trauma. This article reviews the contributions the anthropological literature and the ethnographic case studies of two post‐Hurricane Mitch housing reconstruction sites make to the theorising of community and resilience in post‐disaster reconstruction. Specifically, the article demonstrates that communities are not static or neatly bounded entities that remain constant before, during and after a disaster; rather, communities take on shape and qualities depending on the relationships in which they engage with government agencies and aid organisations before and after disasters. Consequently, the article argues that definitions of community resilience and disaster mitigation programmes must take the emergent and relational nature of communities into account in order to address the long‐term causes and impacts of disasters.